Der semantische Kommentar in gegenwartsbezogenen Sprachkontaktwörterbüchern - Rovere, Giovanni (Zeitschrift für germanistische Linguistik, 2010)
Based on the critical analysis of a specific dictionary, the present paper argues that the comment on semantics in contemporary dictionaries of language contact has to be set up in a completely different manner than that which has been used to date. Dictionaries of this type, which omit the evaluation of corpora as primary sources in favor of secondary sources, reveal systematic shortcomings in the semantic description of contact phenomena. The article focuses specifically on the temporal dimension of marking and the contemporary relevance of the semantic items. The discussed methodological issues are for the most part independent from the respective contact languages, in this case German and Italian, so that the results might be generalized.
Online veröffentlicht: 14.12.2010
Gesehen am 08.01.2021